2010
DOI: 10.1007/s11606-009-1112-8
|View full text |Cite
|
Sign up to set email alerts
|

Are You Ready? How Health Professionals Can Comprehensively Conceptualize Readiness for Change

Abstract: One important factor influencing the successful implementation of system-wide change is initial readiness. Readiness is defined as the degree to which those involved are individually and collectively primed, motivated, and technically capable of executing the change. We present a conceptual framework that highlights three broad areas to be considered if health-care professionals are to comprehensively evaluate readiness that includes psychological factors (i.e., characteristics of those being asked to change),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
242
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(257 citation statements)
references
References 36 publications
8
242
1
6
Order By: Relevance
“…These changes cannot occur if employees are not ready for it." Although some authors suggest that the concept of ORC can be studied at the individual, group, and organizational levels [10,11], those having conducted work on organizational change highlight the relevance of studying collective practices changes at the organizational level [12], considering that these changes can be described as complex because they require multiple simultaneous changes. Although this model has been used generally in the field of health care, to our knowledge the ORC concept appears central and crucial to the study of organizational change specifically targeting schools' regulation and evaluation practices, whether upstream or downstream of the management process.…”
Section: Relevance Of Organizational Readiness For Change Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes cannot occur if employees are not ready for it." Although some authors suggest that the concept of ORC can be studied at the individual, group, and organizational levels [10,11], those having conducted work on organizational change highlight the relevance of studying collective practices changes at the organizational level [12], considering that these changes can be described as complex because they require multiple simultaneous changes. Although this model has been used generally in the field of health care, to our knowledge the ORC concept appears central and crucial to the study of organizational change specifically targeting schools' regulation and evaluation practices, whether upstream or downstream of the management process.…”
Section: Relevance Of Organizational Readiness For Change Conceptmentioning
confidence: 99%
“…In the same vein, Holt et al [11] argued that the concept conduct that defines "how things work here." These beliefs and rules are not always written, and in fact, most of the members of a company would be hard to explain.…”
Section: Orc Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several frameworks for implementing and assessing organizational changes have been constructed (Glasgow et al, 1999;Cohen et al, 2004;Damschroder et al, 2009;Weiner, 2009;Holt et al, 2010). Cohen et al (2004) identified attributes of practices that achieved high rates of intervention adoption and described four major domains (i.e., resources, stakeholder motivation, outside motivators, and opportunities for change) in the Practice Change and Development Model (Cohen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Common to all of them is an emphasis on the importance of context-the recognition that the success of any strategy depends critically on the type of change being implemented and the setting in which it is being adopted. For example, two articles in this supplement deal with the importance of "readiness to change" as an influence on success 8,9 . We need additional practical tools to assess such contextual factors and define how we can address those that are modifiable.…”
mentioning
confidence: 99%